CONSTELLATION ACTOR IN THE DEVELOPMENT OF REGIONAL FREIGHT TRANSPORTATION INFRASTRUCTURE TO SUPPORT EXPORT ACTIVITIES IN TANJUNG PERAK PORT OF SURABAYA - Miming Mihardja; Sri Oka Rachmadita (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2013)
The provision of freight infrastructure linking the hinterland to the port requires agreement between actors. However, in reality there is a policy conflict in the development of a regional freight infrastructure, such as in the case of the Aloha Perak Toll Road construction in Surabaya. This study aims to discuss actor relationship in the freight transport infrastructure development strategy to support export activities in Tanjung Perak Port of Surabaya, using Dynamic Actor Network Analysis. It is found that there is an action conflict in achieving smooth flow of goods coming from the hinterland to the port, particularly between the city of Surabaya Planning Board and the East Java Province Planning Board. The conflict can be minimized by the existence of jujitsu negotiation and BATNA, because the Surabaya City Government, as the owner of the land, has greater power than the Provincial Government.Keywords: regional freight infrastructure, Dynamic Actor Network Analysis, action conflict, conflict management technique